TI_GERICHTE 32.2010.35 vom 9. Dezember 2009 , Irricevibile, in quanto tardivo, il ricorso inoltrato dall'assicurato - TI Tribunale d'appello (2009)
Irricevibile, in quanto tardivo, il ricorso inoltrato dall'assicurato